Intestinal mass in a one year old child: An unusual presentation of Strongyloides stercolaris infection. Case report - Silvia Aragon, MD; Juan Valero, MD; Lina Eugenia Jaramillo, MD (Elsevier, 2017)
Intestinal strongyloidiasis is a common disease in the world. In children, the worldwide prevalence rates ranged from 0.6% to 5.3% [1]. In Colombia studies report a prevalence of 1.3% in children, although it may be higher [2]. The most frequent symptoms are abdominal pain, diarrhea and weight loss. However, on rare occasions the infection can cause duodenal obstruction, pyloric hypertrophy and colonic mass. This article reports the first case of a toddler who presented with a mass in the cecum as a manifestation of Strongyloides stercolaris infection, which required surgical resection as it was initially believed to be a Burkitt lymphoma.